Maturation of mismatch negativity and P3a response across adolescence. (5th February 2015) - Mahajan, Yatin; McArthur, Genevieve
Highlights: The MMN did not change reliably across adolescence. The amplitude and latency of P3a reduced across adolescence. The ability to orient towards an unexpected sound continues to develop across adolescence. Abstract: Adolescents experience significant changes in various physiological and psychological domains due to changes in their brain's structure and function. A lot is known about structural changes in the brain across adolescence. However, less research has investigated changes in brain function during this period. In this study, we tracked the maturation of the auditory mismatch negativity (MMN) and P3a brain responses – both posited as neural indices of auditory discrimination – in 90 adolescents aged 10–18 years. We found that P3a mean amplitude and latency decreased significantly across adolescence, but there was no reliable change in the MMN. These results suggest that neural processes associated with passive auditory processing continue to develop well into adolescence.